MULTIVARIATE DATA ANALYSIS FOR FORCE-, DISPLACEMENT-, AND PERFORMANCE-BASED SEISMIC DESIGN OF REINFORCED MASONRY SHEAR WALLS - Siam, Ahmad Sabry (My University, 2017)
Over the past decades, seismic analysis and design have been thoroughly addressed by the majority of international building codes and standards. Although seismic damage of structural components typically correlate better to displacement, rather than forces, current seismic codes adopt force-based seismic design (FBSD) approaches. However, in the past two decades, there has been a gradual shift from “strength” to “performance” through the introduction of performance-based seismic deign (PBSD) of structural components that can be implemented with relative ease through displacement-based seismic design (DBSD) approaches. For reinforcement masonry shear wall (RMSW), several gaps still exist in implementing FBSD, DBSD and PBSD. Some of these gaps include: quantifying the reliability of the ductility-related parameters when a FBSD approach is adopted; quantifying a reliable maximum lateral load displacement when a DBSD approach is implemented; developing a backbone curve model so that different damage states can be identified when implementing PBSD approach. As such, this dissertation attempts to tackle these issues within the different seismic design approaches. For FBSD, this study assesses the reliability of eight published plastic hinge models using a large database of experimentally tested RMSW. In addition to assessing model reliability in terms of displacement predictability, this dissertation also specifies calibration factors to further improve the evaluated models. For DBSD, multivariate data analysis technique through the principal component analysis (PCA) technique and partial least square (PLS) analysis technique is utilized to develop an experimentally calibrated RMSW displacement prediction expressions for both the maximum lateral load limit state and the ultimate displacement limit state. These expressions are further utilized to evaluate the parameters influencing RMSW displacement capacities. For PBSD, complete backbone curve model for RMSW under lateral loads is developed in this dissertation and subsequently utilized to generate an analytical RMSW performance database. This large database is further utilized to generate seismic fragility bands that are compared to the FEMA P-58 fragility curves in an effort to represent a more realistic means of quantifying RMSW performance and damage states under different seismic demand levels.